Satisfaction Among Gen Y patients: a case study of students at the International Islamic University Malaysia - Abd. Manaf, Noor Hazilah; Mohd, Dinon; Abdullah, Kalthom (Emerald Group Publishing, 2010)
Purpose – The purpose of this paper is to assess satisfaction of Generation Y (Gen Y) patients in Malaysia. Design/methodology/approach – A patient satisfaction study was conducted on an outpatient clinic at the Health Centre of the International Islamic University Malaysia (IIUM). The majority of students at the IIUM comprise undergraduates who are within the age group categorised as Gen Y. Patient satisfaction questionnaire was used as the main method of data collection. The survey was administered to patients over a two-week period during regular semester session. Findings – More than 85 per cent of the respondents are below 25 years of age, reflecting the Gen Y demography. Significant difference is found in the level of satisfaction on the service of doctors between the younger Gen Y undergraduate students and postgraduate students; as well as the Gen Y and the employees. Level of confidence in the clinic is also lower among those of the Gen Y age group, reflecting the higher expectation of service quality. Originality/value – Patient satisfaction is an important measure of the quality of care provided by healthcare organisations.Understanding the needs of a target group of patients can be used for continuous improvement where their specific needs and expectations can be addressed. A study on patient satisfaction among the Gen Y has been rarely explored. The study is an early attempt in filling the void. Keywords Age groups, Patients, Customer satisfaction, Customer services quality, Educational institutions, Malaysia Paper type Research paper